2015
DOI: 10.3920/cep150015
|View full text |Cite
|
Sign up to set email alerts
|

Small and medium agility dogs alter their kinematics when the distance between hurdles differs

Abstract: There is currently a lack of research examining the health and welfare implications for competitive agility dogs. The aim of this study was to examine if jump kinematics and apparent joint angles in medium (351-430 mm to the withers) and small (<350 mm to the withers) agility dogs altered when distances between consecutive upright hurdles differ. Dogs ran a course of nine hurdles; three set at 3.6 m apart; three at 4 m apart and three at 5 m apart. Both medium (P=0.044) and small (P=0.006) dogs landed close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Consequently, to clear a single hurdle, long and quick jumps should be considered as positive. It has been shown that beginner dogs jumped slower than higher-skilled dogs, illustrating how speed may contribute to dogs advancing up a competitive level or, arguably, how speed will increase with skill [11]. In the present study, dogs in group A showed longer and quicker jumps than dogs in group B.…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…Consequently, to clear a single hurdle, long and quick jumps should be considered as positive. It has been shown that beginner dogs jumped slower than higher-skilled dogs, illustrating how speed may contribute to dogs advancing up a competitive level or, arguably, how speed will increase with skill [11]. In the present study, dogs in group A showed longer and quicker jumps than dogs in group B.…”
Section: Discussionsupporting
confidence: 43%
“…Several similar studies have used markers glued on the dog’s skin as anatomical references [ 10 , 14 ]. In order to create greater feasibility and a simpler recording procedure as found in similar studies [ 11 , 12 , 13 , 15 ], we did not use markers. However, the anatomical references used in the present study could be easily located in the video images, as they were in the cited studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations